A determination method for the shear strength of soil-rock mixture considering the size effect and its application - Zhou, Yingbo; Sheng, Genlin; Qiao, Shihui; Zhou, Li; Cai, Jie; Xu, Hanping (Frontiers in Materials, 2022)
The shear strength of the soil-rock mixture (S-RM) is the primary mechanical factor influencing the stability of the deposit slope. The particle size range inside the test sample, however, is not the same as that of the S-RM in the deposit slope due to the limitations of the test device, which results in a variation in the mechanical properties. In this study, computer simulation tests were conducted to examine the impact of particle size on mechanical behaviors under the uniaxial compressive condition, and the size effect was analyzed from both macroscopic and mesoscopic perspectives. Results indicate that when the particle size increases, the anisotropy levels of the S-RM sample also rise, causing the particle displacement difference inside the sample to increase and the rounding rock effect to become more pronounced. The quantitative relationship between the uniaxial compressive strength (UCS) and the maximum particle size (dmax) was proposed, and the accuracy of the prediction formula for the UCS value of S-RM that takes the size effect into account has been confirmed. The improvement of the shear strength determination method was achieved by unifying the particle size range corresponding to the uniaxial compressive and shear test results used in the approach, and the determination method was used to evaluate the stability of a typical deposit slope. The study results can be used as a guide for estimating strength parameters of S-RM throughout the design and construction process of the deposit slope.